Equity research LATAM airlines group: equity report - Maasch, Lukas (2020)
This report contains the description of a valuation performed on LATAM Airlines, the largest airline in South America. This study was conducted by analyzing the factors that may affect the company’s value. In this individual part a deep-dive into the possibility of default in gwas performed. This risk is perceived as substantial. An estimated share price of 2.26$ (the target value for the 31st of December 2020) was computed, which leads us to recommend investors to sell their position in LATAM Airlines.